Optimizing Environmental Policy: Bioremediation as an Eco-friendly Solution for Wastewater Treatment in the Yogyakarta Batik Industry - Dewi, Gayatri Rahma; Lestari, Ani Dwi; Jaladara, Vena (BKM Public Health and Community Medicine, 2024)
Purpose: This abstract aims to describe the non-optimal management practices of batik industry liquid waste in the Yogyakarta area and present eco-friendly solutions for managing batik wastewater. Content: Daerah Istimewa Yogyakarta is one of the leading batik industries in Indonesia, and it has a high-level dyeing production process. Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and the heavy metal Cr(VI) have the potential to threaten public health and environmental sustainability. There needs to be more commitment by batik industry businesses to comply with Perda D.I Yogyakarta No. 7 Tahun 2016 concerning Waste Water Quality Standards. Additionally, insufficient regulatory enforcement by the local government presents a significant obstacle. Limited funds and the high costs of building and operating Wastewater Treatment Plants (IPAL) hamper the management of liquid waste in the batik industry so that it exceeds the standard limits for wastewater quality. A combination of natural filtration (charcoal, gravel, and sand) and bioremediation uses Saccharomyces cerevisiae, which is eco-friendly, affordable, and efficient in reducing BOD, COD, and Cr(VI) levels, effectively separating hazardous substances from batik wastewater. Implementing this solution helps sustain environmental conservation and protect workers from hazards, creating a safe and healthy work environment that enhances the productivity of batik industry workers. There is a cross-sector collaboration between Regional Governments as regulators, rewards, and subsidies for those who implement eco-friendly liquid waste management. DLHK and Disperindagkop play a role in regular monitoring, technical guidance, and providing access to funds for waste management operations, the Association of Indonesian Batik Craftsmen and Entrepreneurs (APPBI) as a mediator between the government and the batik industry, and NGOs as controllers and reporting if violations occur.